Group, team, or something in between? Conceptualising and measuring team entitativity - Vangrieken, Katrien; Boon, Anne; Dochy, Filip; Kyndt, Eva (Frontline Learning Research, 2017)
The main aim of this study includes bridging the gap between strict team and broader group research by describing the distinction between strict teams and mere collections of individuals as the degree of team entitativity or teamness. The concept of entitativity is derived from social psychology research and further developed and integrated in team research. Based upon the entitativity concept and the core team definitions, the defining features shaping teams’ degree of entitativity are determined: shared goals and responsibilities; cohesion (task cohesion and identification); and interdependence (task and outcome). In a next step, a questionnaire is developed to empirically grasp these features. The questionnaire is tested in two waves of data collection (N1=1320; N2=731). Based upon a combination of Classical Test Theory analyses (exploratory and confirmatory factor analyses) and Item Response Theory analyses the questionnaire is developed. The final questionnaire consists of three factors: shared goals and cohesion, task interdependence, and outcome interdependence. Further psychometric analyses include the investigation of validity, longitudinal measurement invariance, and test-retest reliability. This manuscript describes frontline research by: (1) developing a novel conceptualisation bridging groups and teams based upon two research traditions (social psychology and team research) and (2) combining two methodological traditions regarding questionnaire development and validation (Classical Test Theory and Item Response Theory).